MADE BY CHILDREN: THE EXPLOITATION OF CHILD LABOUR IN AGRICULTURE, INDUSTRY AND THE SERVICE SECTOR IN MAINLAND CHINA - Nguyen, Cindy (Faculty of Law, Universitas Brawijaya, 2017)
This research essay examines the exploitation of child labour in agriculture, industry and the service sector in Mainland China. Child productivity in China has historically been essential to the survival of the family. However, the globalized environment has drawn emphasis to the reality that children are exploited and subject to dangerous work conditions. The aim of this research is to analyse the international legal framework and human rights conventions safeguarding the rights of the child. This involved the primary analysis of the Convention on the Rights of the Child, the Minimum Age Convention, the Universal Declaration of Human Rights and the Worst Forms of Child Labour Convention. The Procedure of the Conclusion of Treaties, Minors Protection Law, Provisions on the Prohibition of Using Child Labour, Regulations Banning Child Labour and Compulsory Education Law were critiqued to determine the effectiveness of China's domestic legislation. The results demonstrated that child labour is currently not prohibited under China's domestic law, a consequence of ineffective implementation of international treaties. To support this legal analysis, it evaluated academic research exploring the economic and cultural circumstances of China. It was found that globalization, rapid economic growth, a lack of education and social and cultural constructions of 'child' and 'childhood' further contributed to the existence of child labour. The significance of these findings is that it highlights the difficulty involved in changing legislation when the economic and cultural forces strongly dictate against it. Children are ultimately unable to access justice as effectively as their adult counterparts do within China's legal framework